THE 1948 STATEMENT OF CONCEPTS AND STANDARDS. - Mason, Perry (The Accounting Review, 1950)
Abstract The third attempt of a committee of the American Accounting Association to prepare a systematic statement of accounting concepts and standards deserves much praise and those who are responsible for the drafting of the material should feel that it has made a real contribution. Most of the propositions can be accepted as valid and as contributing toward more effective corporate financial statements. The organization of the material has been improved, particularly by grouping separately the standards to be applied in the preparation of financial statements so that they can be distinguished from the more basic concepts of asset valuation, income determination and the classification and measurement of the equities. It is hoped, however, that an early revision will be published which will incorporate the changes, few though they may be, which seem to have general support. Also, it would be helpful and interesting if the policy were adopted of presenting minority reports. Surely the statement as it stands must be the result of many compromises of differences of opinion. It is doubtful if the time has arrived when one can subscribe without dissent and exception to as many propositions as appear in this statement.